The European Union Trade in Information and Communication Technology in Services with the United States: Evidence from Statistical Data Between 2015 And 2023 - Joanna STEFANIAK; Jacek WINIARSKIand Joseph JANUSZEWICZ (Communications of International Proceedings, 2025)
The European Union-United States ICT services trade relationship has experienced rapid growth, yet existing research predominantly examines aggregate EU-US trade patterns without distinguishing the heterogeneous performance of individual member states in this critical sector. While previous studies acknowledge the EU as an emerging ICT services exporter, limited research systematically analyzes how individual member states' competitive positions and trade specialization patterns evolved during the post-2015 digital transformation period, particularly in bilateral trade with the US market. This study employs Trade Balance Index (TBI) and Revealed Symmetric Comparative Advantage (RSCA) indicators using Eurostat data (2015-2023) to assess both trade positions and export specialization of EU27 member states, applying Widodo's matrix framework to categorize countries into four competitive positions: "Rising Stars," "Untapped Potential," "Weak Players," and "Lagging Opportunities." Results reveal that despite overall EU trade surplus growth from €4.7 billion to €19.3 billion, member states exhibit divergent patterns. Ireland emerged as the dominant exporter (€18.4 billion in 2023) with improved comparative advantage, while Germany remains the only major deficit country. Notably, smaller Central and Eastern European countries demonstrate high export specialization despite modest trade volumes, challenging the assumption that large export volumes guarantee competitive advantage. The analysis identifies 12 "Rising Star" countries in 2023, down from 17 in 2015, indicating increased competitive stratification within the EU's ICT services trade with the United States.
Keywords: ICT services; European Union; United States; trade position; competitive position